Quantification of pancreatic lipomatosis and liver steatosis by MRI: comparison of in/opposed-phase and spectral-spatial excitation techniques - Schwenzer, Nina F; Machann, Jürgen; Martirosian, Petros; Stefan, Norbert; Schraml, Christina; Fritsche, Andreas; Claussen, Claus D; Schick, Fritz (Investigative radiology, 2008)
The goal of the present study was the assessment of pancreatic and hepatic fat content applying 2 established magnetic resonance (MR) imaging techniques: in-phase/opposed-phase gradient-echo MR imaging and fat-selective spectral-spatial gradient-echo imaging. Results of both approaches were compared, and influences of T1- and T2*-related corrections were assessed. The possibility of a correlation between pancreatic lipomatosis and liver steatosis was investigated. Seventeen volunteers at risk for type 2 diabetes (6 male, 11 female; age, 26-70 years; body mass index, 19.4-41.3 kg/m2; mean, 31.7 kg/m2) were examined. Liver and pancreas fat content were quantified with 2 different gradient-echo techniques: one uses a spectral-spatial excitation technique with 6 binomial radio frequency pulses, which combines chemical shift selectivity with simultaneous slice-selective excitation. The other technique based on double-echo chemical shift gradient-echo MR provides in- and opposed-phase images simultaneously. Influences of T1 and individual T2* effects on results using in-phase/opposed-phase imaging were estimated and corrected for, based on additional T2* measurements. The fat content calculated from images recorded with the fat-selective spectral-spatial gradient-echo sequence correlated well with the fat fraction determined with in-phase/opposed-phase imaging and following correction for T1/T2* effects: pancreas r = 0.93 (P < 0.0001) and liver r = 0.96 (P < 0.0001). In-phase/opposed-phase imaging revealed a pancreatic fat content between 1.6% and 22.2% (mean, 8.8% +/- 5.7%) and a hepatic fat fraction between 0.6% and 33.3% (mean, 7.9% +/- 9.1%). The fat-selective spectral-spatial gradient-echo sequence revealed a pancreatic lipid content between 3.4% and 16.1% (mean, 9.8% +/- 4.0%) and a hepatic fat content between 0% and 28.5% (mean, 8.8% +/- 8.3%). With neither technique was a substantial correlation between pancreatic and hepatic fat content found. The presented results suggest that both methods are reliable tools for pancreatic and hepatic fat quantification. However, for reliable assessment of quantitative fat by the in-phase/opposed-phase technique, an additional measurement of T2* seems crucial.